2018
DOI: 10.1186/s13045-017-0553-5
|View full text |Cite
|
Sign up to set email alerts
|

CAR-T cells targeting CLL-1 as an approach to treat acute myeloid leukemia

Abstract: BackgroundAcute myeloid leukemia (AML) is one of the most common types of adult acute leukemia. Standard chemotherapies can induce complete remission in selected patients; however, a majority of patients eventually relapse and succumb to the disease. Thus, the development of novel therapeutics for AML is urgently needed. Human C-type lectin-like molecule-1 (CLL-1) is a type II transmembrane glycoprotein, and its expression is restricted to myeloid cells and the majority of AML blasts. Moreover, CLL-1 is expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 46 publications
(32 reference statements)
0
124
0
1
Order By: Relevance
“…In addition, we have recently shown the relevance of the marker in myelodysplastic syndrome (MDS) and pointed out important differences in the applicability of the marker in these biologically different disease entities (Toft-Petersen et al, 2016). Given this, the CLEC12A receptor is an attractive treatment target in AML, and current developments in this regard include both CLEC12A-CD3 bispecific antibodies (Lu et al, 2014;Leong et al, 2017) and chimeric antigen receptor (CAR)-engineered T-cells (CAR-T-cells) directed against CLEC12A (Laborda et al, 2017;Tashiro et al, 2017;Wang et al, 2018) and, most recently, the development of a novel antibody-drug conjugate (Jiang et al, 2018).…”
Section: Research Papermentioning
confidence: 99%
“…In addition, we have recently shown the relevance of the marker in myelodysplastic syndrome (MDS) and pointed out important differences in the applicability of the marker in these biologically different disease entities (Toft-Petersen et al, 2016). Given this, the CLEC12A receptor is an attractive treatment target in AML, and current developments in this regard include both CLEC12A-CD3 bispecific antibodies (Lu et al, 2014;Leong et al, 2017) and chimeric antigen receptor (CAR)-engineered T-cells (CAR-T-cells) directed against CLEC12A (Laborda et al, 2017;Tashiro et al, 2017;Wang et al, 2018) and, most recently, the development of a novel antibody-drug conjugate (Jiang et al, 2018).…”
Section: Research Papermentioning
confidence: 99%
“…An additional limitation in AML has been the lack of ideal target antigens, which hinders the use of ADCC, T cell engaging techniques, and CAR (chimeric antigen receptor) T‐cells. Nonetheless, there are numerous ongoing trials investigating the role of CAR T‐cells for AML, with major targets including CD33, CD123, CLL‐1, and FLT3 . Similarly, T‐cell engaging techniques are now being used in AML, mostly targeting CD33 and CD123 .…”
Section: Discussionmentioning
confidence: 99%
“…Much the same applies to the developing literature on targeting the CLEC12A receptor (Zhao et al , ; Lu et al , ; Laborda et al , ; Leong et al , ; Tashiro et al , ; Wang et al , ), which has also been shown to be absent on the most immature HSPCs in normal bone marrow (van Rhenen et al , ; Bill et al , ). Recent efforts in targeting this marker include the development of cytotoxic monoclonal antibodies (Zhao et al , ) and CLEC12A‐CD3 bispecific antibodies (Lu et al , ; Leong et al , ).…”
Section: Biological Differences Between Normal Haematopoiesis and Lscmentioning
confidence: 93%
“…A first‐in‐human phase 1 clinical trial of a bispecific CLEC12A‐CD3 antibody for the treatment of relapsed/refractory AML or previously untreated elderly AML patients is currently recruiting (NCT03038230). In addition, the recently developed chimeric antigen receptor (CAR) engineered T cells (CAR‐T cells) directed against CLEC12A (Laborda et al , , Tashiro et al , , Wang et al, ) and toxin‐conjugated antibodies also seem promising (Jiang et al , ). Taken together – and given the success of other antibody‐based initiatives, most prominently rituximab – this line of anti‐LSC targeting is definitely one to follow.…”
Section: Biological Differences Between Normal Haematopoiesis and Lscmentioning
confidence: 99%